Stereoselective Binding of Human Serum Albumin - Chuang, Victor; Otagiri, M. (Wiley-Liss, 2006)
Stereoselectivity in binding can have a significant effect on the drug disposition such as first-pass metabolism, metabolic clearance, renal clearance, and protein and tissue binding. Human serum albumin (HSA) is able to stereoselectively bind a great number of various endogenous and exogenous compounds. Various experimental data suggested that the two major drug-binding cavities, namely, site I and site II, do not seem to be the stereoselective binding sites of HSA. Stereoselective binding of HSA under disease conditions such as renal and hepatic diseases was found to be enhanced. In addition, site-to-site displacement of a site II-specific drug by another site II-specific drug was found to be stereoselective, too. Endogenous compounds such as long-chain fatty acids and uremic toxins are likely to cause combined direct and cascade effects that contribute to the preferential binding of a particular drug enantiomer. Taking together the findings of other studies, it is highly possible that the stereoselective binding site exists at the interface of the subdomains.